2018
DOI: 10.3892/ijo.2018.4596
|View full text |Cite
|
Sign up to set email alerts
|

Direct comparison of 2‑amino[3‑11C]isobutyric acid and 2‑amino[11C]methyl‑isobutyric acid uptake in eight lung cancer xenograft models

Abstract: The non-natural amino acid positron emission tomography tracers, 2-amino[3-11 C]isobutyric acid ([3-11 C] AIB) and 2-amino[ 11 C]methyl-isobutyric acid ([ 11 C]MeAIB), are metabolically stable in vivo and accumulate in tumors. [3-11 C]AIB is transported into cells mainly via the amino acid transport system A and partially via systems L and ASC, whereas [ 11 C]MeAIB is transported into cells specifically via system A. How transport via the different systems affects the tumor uptake of these tracers, however, is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…In this study, we revealed that butyric acid had the strongest antitumor activity among butyric acid, isobutyric acid and acetic acid SCFAs. Most reports on the antitumor activity of SCFAs are for butyric acid (6,7) or isobutyric acid (16). This is the first report on the comprehensive analysis of the mechanism of the antitumor action of butyric acid, isobutyric acid, and acetic acid in human colon cancer cells.…”
Section: Discussionmentioning
confidence: 91%
“…In this study, we revealed that butyric acid had the strongest antitumor activity among butyric acid, isobutyric acid and acetic acid SCFAs. Most reports on the antitumor activity of SCFAs are for butyric acid (6,7) or isobutyric acid (16). This is the first report on the comprehensive analysis of the mechanism of the antitumor action of butyric acid, isobutyric acid, and acetic acid in human colon cancer cells.…”
Section: Discussionmentioning
confidence: 91%
“…Amino acids, vital for the survival of all types of cells, serve as a source of energy, participate in biosynthesis, and contribute to maintaining redox balance [9,10,29]. Amino acid-based radiopharmaceuticals are widely used in PET [1,2,6,8,9,[30][31][32], and are regarded as markers of tumor proliferation, since tumor cells actively accumulate amino acids due to the activation of specific transmembrane transporters [9,10,29]. Amino acids can be used to label various metabolic processes in the brain [9,10].…”
Section: Amino Acid Metabolism In Healthy Brain Tissue and In The Tumorsmentioning
confidence: 99%